ANALISIS FORENSIK KEGAGALAN KONSTRUKSI STRUKTUR BANGUNAN 3 LANTAI DENGAN SAP (STRUCTURE ANALYSIS PROGRAM) 2000 - tatang kukuh wibawa; Ilham Syaekhul Amri (Pusat Laboratorium Forensik adan Reserse Kriminal Kepolisian Negara Republik Indonesia, 2021)
A Building 3-storey construction project using reinforced concrete construction was failure and collapse in Johor Baru Central Jakarta. The impact of construction failure is work accidents (injury and death), damage to construction/infrastructure, and there are legal consequences for failures that occur and the causes of failure. The research method is to examine the condition of the installed structure, check the level of damage, test the quality of concrete, structural modeling with SAP (Structure Analysis Program) 2000, analyze and calculate the strength of the column cross section, analyze and conclude from the overall inspection results with implementing regulations and reinforcement in SNI 03 -2847-2002. The results of the study concluded that the initial failure was in the column with a size of 33 x 10 centimeters on the south side of the 1st floor with a buckling type failure that caused it to collapse due to pressure from above (floors 2 and 3). The results of the structural modeling of the SAP 2000 program and the calculation of the column cross-sectional strength obtained that the cross-sectional strength capacity of the column is 32.80 tons, this value is still able/safe to withstand the load of the structure above it. The failure and collapse of the column was caused by the implementation of the principles and details of the reinforcement that were not standardized and did not follow the rules of SNI 2847:2013 on the spacing of the stirrups and the details of bending of the iron.